Comparative Genomic Analysis Reveals the Metabolism and Evolution of the Thermophilic Archaeal Genus Metallosphaera - Wang, Pei; Li, Liang Zhi; Qin, Ya Ling; Liang, Zong Lin; Li, Xiu Tong; Yin, Hua Qun; Liu, Li Jun; Liu, Shuang-Jiang; Jiang, Cheng-Ying (Frontiers in Microbiology, 2020)
Members of the genus Metallosphaera are widely found in sulfur-rich and metal-laden environments, but their physiological and ecological roles remain poorly understood. Here we sequenced Metallosphaera tengchongensis Ric-A, a strain isolated from the Tengchong hot spring in Yunnan province, China, and performed a comparative genome analysis with other Metallosphaera genomes. The genome of M. tengchongensis had an average nucleotide identity (ANI) of approximately 70% to that of M. cuprina. Genes sqr, tth, sir, tqo, hdr, tst, soe and sdo associated with sulfur oxidation, and genes clusters fox, cbs involved in iron oxidation existed in all Metallosphaera genomes. However, the adenosine-5’-phosphosulfate (APS) pathway was only detected in M. sedula and M. yellowstonensis, and several subunits of fox cluster were lost in M. cuprina. Complete 3-hydroxypropionate/4-hydroxybutyrate cycle and dicarboxylate/4-hydroxybutyrate cycle involved in carbon fixation were found in all Metallosphaera genomes. A large number of gene family gain events occurred in M. yellowstonensis and M. sedula, whereas gene family loss events occurred frequently in M. cuprina. Pervasive strong purifying selection was found acting on the gene families of Metallosphaera, of which transcription-related genes underwent the strongest purifying selection. In contrast, genes related to prophages, transposons, and defense mechanisms were under weaker purifying pressure. Taken together, this study expands knowledge of the genomic traits of Metallosphaera species and sheds light on their evolution.